Intraoperative Error Propagation in 3-Dimensional Spinal Navigation From Nonsegmental Registration: A Prospective Cadaveric and Clinical Study. Issue 5 (August 2019) - Guha, Daipayan; Jakubovic, Raphael; Gupta, Shaurya; Fehlings, Michael G.; Mainprize, Todd G.; Yee, Albert; Yang, Victor X. D.
Study Design: Prospective pre-clinical and clinical cohort study. Objectives: Current spinal navigation systems rely on a dynamic reference frame (DRF) for image-to-patient registration and tool tracking. Working distant to a DRF may generate inaccuracy. Here we quantitate predictors of navigation error as a function of distance from the registered vertebral level, and from intersegmental mobility due to surgical manipulation and patient respiration. Methods: Navigation errors from working distant to the registered level, and from surgical manipulation, were quantified in 4 human cadavers. The 3-dimensional (3D) position of a tracked tool tip at 0 to 5 levels from the DRF, and during targeting of pedicle screw tracts, was captured in real-time by an optical navigation system. Respiration-induced vertebral motion was quantified from 10 clinical cases of open posterior instrumentation. The 3D position of a custom spinous-process clamp was tracked over 12 respiratory cycles. Results: An increase in mean 3D navigation error of ≥2 mm was observed at ≥2 levels from the DRF in the cervical and lumbar spine. Mean ± SD displacement due to surgical manipulation was 1.55 ± 1.13 mm in 3D across all levels, ≥2 mm in 17.4%, 19.2%, and 38.5% of levels in the cervical, thoracic, and lumbar spine, respectively. Mean ± SD respiration-induced 3D motion was 1.96 ± 1.32 mm, greatest in the lower thoracic spine ( P < .001). Tidal volume and positive end-expiratory pressure correlated positively with increased vertebral displacement. Conclusions: Vertebral motion is unaccounted for during image-guided surgery when performed at levels distant from the DRF. Navigating instrumentation within 2 levels of the DRF likely minimizes the risk of navigation error.